Հայերի ունեզրկումը Օսմանյան կայսրությունում (1914–1923 թթ.) - Անահիտ Աստոյան (ՀՀ ԳԱԱ հրատ.)
Геноцид армян сопровождался грабежом движимого и недвижимого имущества армян. Свидетельства запланированного грабежа со стороны государства есть как в рассказах выживших и в рапортах действующих на территории Османской империи дипломатов, так и в турецких источниках, которые доказывают, что важнейшим мотивом истребления армянского народа была экспроприация имущества армян. During the Armenian Genocide the movable and immovable properties of Armenians were robbed. Abound testimonials about this planned plunder are left by the survivors, in the reports of the diplomats who were operating on the territory of the Ottoman Empire, as well as in the Turkish sources, which confirm that the expropriation of Armenians’ properties was a crucial motive for the extermination of the Armenian nation.
Keywords: History; Armenian Genocide (1915); D History; H Social Sciences; HC Economic History and Conditions